2001
DOI: 10.4269/ajtmh.2001.65.747
|View full text |Cite
|
Sign up to set email alerts
|

The appearance of a second genotype of Japanese encephalitis virus in the Australasian region.

Abstract: In mid-January 2000, the reappearance of Japanese encephalitis (JE) virus activity in the Australasian region was first demonstrated by the isolation of JE virus from 3 sentinel pigs on Badu Island in the Torres Strait. Further evidence of JE virus activity was revealed through the isolation of JE virus from Culex gelidus mosquitoes collected on Badu Island and the detection of specific JE virus neutralizing antibodies in 3 pigs from Saint Pauls community on Moa Island. Nucleotide sequencing and phylogenetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
84
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 29 publications
0
84
0
1
Order By: Relevance
“…Moreover, a doubt remains on the year. The year of isolation is more often cited in studies (for instance Pyke et al, 2001) while in GenBank database, the year of collection is sometimes given (for instance strains LY5P-09 and YN114, respectively presented in Zhang et al, 2011 andWang et al, 2010). Even, in other articles, the term year alone is used and serves as an element of description of the history of the strains (for instance Yun et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a doubt remains on the year. The year of isolation is more often cited in studies (for instance Pyke et al, 2001) while in GenBank database, the year of collection is sometimes given (for instance strains LY5P-09 and YN114, respectively presented in Zhang et al, 2011 andWang et al, 2010). Even, in other articles, the term year alone is used and serves as an element of description of the history of the strains (for instance Yun et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several more recent observations tend to discard this hypothesis and suggest that genotypes could be found indifferently within former epidemic or endemic area. Thus, two JEV strains belonging to GI were isolated in the Australasian region (Pyke et al, 2001) and strains of the genotype II have been shown to use to circulate in Korea before 1970's (Schuh et al, 2010(Schuh et al, , 2011.…”
mentioning
confidence: 99%
“…The occurrence of JEV genotypes I and III in northern regions and II and IV in southern regions led to the proposal that different genotypes may explain the differing clinical epidemiology (Chen et al, 1990(Chen et al, , 1992. However, the recent arrival of a 'northern genotype I' isolate in Australia (Pyke et al, 2001), the observation that genotype III is associated with epidemic disease in northern Vietnam and endemic disease in southern Vietnam (Solomon et al, 2000a), and the idenitification of a putative V genotype (Uchil and Satchidanandam, 2001) suggest the current paradigm may need revising.…”
Section: Clinical Epidemiologymentioning
confidence: 99%
“…3). Eventually, genotype I, which is genetically close to those from Malaysia, was found to have been introduced and co-circulated with and/or ultimately replaced the existing genotype III in many Asian countries (Fulmali et al, 2011;Huang et al, 2010;Ma et al, 2003;Nga et al, 2004;Pyke et al, 2001;Wang et al, 2007;Yoshida et al, 2005;Yun et al, 2010). Putatively, the introduced genotype I originated from Southeast Asia (Nabeshima et al, 2009;Nga et al, 2004); which has been an important region for emerging pathogens (Solomon et al, 2003).…”
Section: Origin and Genetic Diversity Of The Jevmentioning
confidence: 99%
“…2); these probably originated from the ancestral virus and evolved into the different genotypes (Solomon et al, 2003). Geographically, genotype I includes isolates from Korea, India, Cambodia, Laos, and northern Thailand (Fan et al, 2010;Fulmali et al, 2011;Wang et al, 2007Wang et al, , 2010); genotype II includes isolates from Malaysia, Sarawak, Indonesia, southern Thailand, and northern Australia (Pyke et al, 2001); genotype III includes isolates widely distributed in Asian countries with temperate climates, including Japan, Taiwan, China, India, Sri Lanka, Nepal, Viet Nam, and the Philippines (Chen et al, 1990;Mackenzie et al, 2004;Wang et al, 2007); and genotype IV includes isolates from Indonesia (Chen et al, 1992). The last one identified was genotype V, which includes isolates with a restricted distribution in India (Solomon et al, 2003;Uchil & Satchidanandam, 2001).…”
Section: Origin and Genetic Diversity Of The Jevmentioning
confidence: 99%